Personalizing text by using readers’ names – effects on reading comprehension and social agency: Personalizing text by using readers’ names – effects on reading comprehension and social agency - Lindhaus, Maike; Ehlert, Mareike; Dutke, Stephan (European journal of psychology of education, 2025)
Personalizing text is known to support learning from text. The present study extends evidence of the personalization effect by investigating whether elementary school students’ reading comprehension benefits from reading narratives personalized by using the reader’s name for the narrative’s protagonist. Additionally, this study examined the influence of personalization on social agency and tested the hypothesis that social agency mediated the personalization effect. For this purpose, N = 96 elementary school students were tested. Fifty-one students read a narrative in which the protagonist shared the reader’s first name, while the control group ( n = 45) read a narrative with a protagonist who had a different name. Reading comprehension was assessed using a standardized test that measured both text recall and transfer performance. Readers of the personalized narrative showed significantly higher text transfer and higher social agency ratings. Social agency was found to mediate the personalization effect on text transfer. These findings suggest that personalizing reading materials for elementary school students can enhance their reading comprehension by increasing their sense of social agency.